EFFECT OF TIME INTERVAL OF DEPURATION ON NUTRIENTS, HEAVY METALS AND MICROBIAL CONTENTS OF PERIWINKLES FROM ELECHI CREEK, RIVERS STATE, NIGERIA - OJINNAKA, M.C; OKEREKE, A.N.; OJIMELUKWE, P.C.; ANI, O.M.; KANU, N.N.; NJOKU, E.C.; OCHIOGU, S.O.; OKEREAFOR, O.C.; ONYEJIUWA, N.C. (Nigerian Journal of Fisheries, 2020)
The present study investigated the effects of time interval of depuration on nutrients, heavy metals and microbial contents of periwinkles from Elechi creek using tap water. The physico-chemical parameters of the tap water used for depuration were also determined. There were decreases in the microbial populations from 0 h to 24 h depuration. The vibrio bacteria reduced from 0 h to 48 h (6.66 x107cfu/ml-1 to 1.16 x107cfu/ml-1). The faecal coliform bacteria were not detected (0.00 x102cfu/ml-1). The total heterotrophic bacteria was highest at 0 h depuration with 33.6 x107cfu/ml-1 but reduced to 3.43 x107cfu/ml-1 at 24h depuration process. The heavy metals (chromium, cadmium,lead) investigated were of lower values howeverlead and chromium were not detected from the depurated and non-depurated periwinkle samples. Cadmium contents were in the range of 0.97 – 0.11 mg/kg. The protein content of the periwinkle samples increased as the depuration time progressed (14.42 – 14.72%). The moisture content ranged from 81.41 – 82.28%. The results from the physico-chemical parameters showed that there were significant (P>0.05) increases in the pH (6.80 – 7.77), dissolved oxygen (4.82 – 5.89 mg/l) and salinity (4.28 – 5.72 mg/l) while the temperature decreased from 28.0 – 27.8oC. There were no turbidity values detected.